Perancangan Ulang UI/UX Hotel Duta Garden Berbasis Website dengan Metode User-Centered Design Untuk Meningkatkan Pengalaman Pengguna - Ilyas, Diki Akhmad; Mushlihudin, Mushlihudin (Journal of Information System Research (JOSH), 2024)
Information technology has developed rapidly in facilitating people to exchange information and also do business through websites. Hotel Duta Garden is one of the commercial businesses that focuses on providing services for guests or tourists in the Yogyakarta area. Based on the results of the questionnaire that has been analyzed, users highly appreciate accurate information and attractive visual design in the online hotel booking experience. This supports the interface design that is designed to provide a more structured and informative experience for users.This study aims to enhance the UI/UX quality of the Duta Garden Hotel Yogyakarta website by applying the User-Centered Design (UCD) approach. The redesign focuses on improving usability, better information visualization, and enhancing the User experience during the booking process through the website. The redesign process covers key aspects such as navigation, page layout, and user interaction, with an emphasis on optimizing the desktop version. Testing was conducted using the System usability scale (SUS) through two scenarios: room booking and error notification. The evaluation results indicate that the new design significantly improved user satisfaction, with an average SUS score of 90 for scenario booking and 81 for scenario error notification. Recommendations for further improvement were also provided based on findings during the testing process.